Entre a sacramentalização católica e outros arranjos parentais: a vida familiar dos escravizados do Crato-CE (1871-1884) - Tavares, Iris Mariano (2013)
This dissertation is linked to the online research Regional History, the Post-Graduate in History of the Federal University of Paraíba, with a major in History and Historical Culture. Is engaged in the family life of enslaved the city of Crato, Ceará south. The time frame chosen starts in 1871, the year of enactment of Law 2040 of September 28 - also known as the Rio Branco Law or Law of the Free Womb - and ends in 1884, the year it was declared abolished slavery in the province of Ceará. The spread of unions sacramentadas the religious norm and consensus among the enslaved population, the stability of family arrangements that were able to provide, and the social relations established in the act of baptism of their children, are also observed. Sources that support the research are mainly, inventories - with lists of registration of enslaved and autos sharing, attached to them -, and seats baptism of naive cratenses. The dissertation is theoretical and methodological social history of slavery, developed mainly from the 1980s and whose assumptions highlight the historical subjects - the enslaved.